Income inequality, household consumption and status competition in Germany - Jan Behringer; Lukas Endres; Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2023)
We analyse the decline of household saving rates in the bottom half of the income distribution in Germany since the 2000s, which allowed for only moderately increasing consumption inequality, despite sharply rising income inequality. We combine survey data on household consumption with our own representative survey on the visibility and status relevance of various spending categories to test for upwards directed social status comparisons as an explanation of these trends. We find that non-rich households shift their income allocations towards more visible and status relevant areas of consumption when incomes at the top rise relative to their own. Renter households offset higher status consumption by reducing expenditures on other consumption components. In contrast, homeowners maintain higher status-oriented expenditures, particularly regarding housing, by considerably reducing their saving rates.
Keywords: D1; D31; E21; R21; 330; Personal Income Distribution; Status Concerns; Household Consumption; Homeownership